The actor's book of contemporary stage monologues - Shengold, Nina. (New York : Penguin Books, 1987)
A collection of monologues from the 1960s to the 1980s that may be used for auditions and classwork. Included are works from off-Broadway, off-off-Broadway, and regional theaters written by authors such as Tennessee Williams, Sam Shepard, David Rabe, Charles Fuller, and Landford Wilson.
The actor's nightmare / Christopher Durang -- Aunt Dan and Lemon / Wallace Shawn -- Birdbath / Leonard Melfi -- Bosoms and neglect / John Guare -- The dance and the railroad / David Henry Hwang -- Gemini / Albert Innaurato -- Lakeboat / David Mamet -- Loose ends / Michael Weller -- Old times / Harold Pinter -- Reckless / Craig Lucas.
"A Smith and Kraus Inc. book."
School Library Journal
Kirkus Review
Young Adult
Keywords: Monologues